2017
DOI: 10.1016/j.appet.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of Mindfulness Based Stress Reduction for emotional eating

Abstract: Emotional eating is an important predictor of weight loss and weight regain after weight loss. This two part study’s primary aim was to explore changes in emotional eating in a general population of individuals taking the Mindfulness Based Stress Reduction (MBSR) program, with a secondary aim to explore whether changes in mindfulness predicted changes in emotional eating. Self-reported survey data exploring these questions were collected before and after the intervention for two sequential studies (Study 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
2
20
0
5
Order By: Relevance
“…To date, mindfulness-based interventions for weight loss have indicated that adding a mindfulness component to weight-loss interventions has the potential to strengthen their effectiveness [44,47,48,50,52]. The current study presented a case for mindfulness training occurring before weight loss is attempted, to specifically address psychological traits that underpin overeating and undermine weightloss efforts.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…To date, mindfulness-based interventions for weight loss have indicated that adding a mindfulness component to weight-loss interventions has the potential to strengthen their effectiveness [44,47,48,50,52]. The current study presented a case for mindfulness training occurring before weight loss is attempted, to specifically address psychological traits that underpin overeating and undermine weightloss efforts.…”
Section: Discussionmentioning
confidence: 95%
“…In effect they became more "in-tune" with or aware of the influence of external and internal triggers to eat, obtained distance from the influence of aversive emotions, in effect becoming less reactive, and developed enhanced control over impulsive urges. This explanation can be supported in part by the evidence reviewed regarding the positive effects of mindfulness on varied measures of cue-driven and emotional eating [31,32,44,49,50,[56][57][58][59]. However, until a randomized trial is conducted to disentangle the meditation and educational elements compared to an active control such conclusions warrant cautious interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Levoy, Lazaridou, Brewer, and Fulwiler () reported that treatment for reducing mental stress reduces emotional exertion. In a part of their findings, de Jong et al () reported that cognitive‐based therapy would lead to body awareness and reduce depression.…”
Section: Introductionmentioning
confidence: 99%